Rhenium(I) tricarbonyl complex of 5,20-bis(p-tolyl)-10,15-bis(p-methoxyphenyl)-21-selenaporphyrin: first X-ray structural characterization of metal complex of 21-selenaporphyrin - Ghosh, Avijit; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Dalton Transactions, 2013)
Synthesis and first structural characterization of hexa coordinated rhenium(I)tricarbonyl complex of 5,20-bis( p-tolyl)-10,15-bis(p-methoxyphenyl)-21-selenaporphyrin 3 are described. The Re(I)complex of 21-selenaporphyrin 3 was synthesized by treating free base 21-selenaporphyrin in 1,2-dichlorobenzene with Re(CO)(5)Cl at reflux for 7 h and analyzed using mass, NMR, FT-IR, UV-vis and electrochemical techniques. The first structure of metal complex of 21-selenaporphyrin was determined by X-ray single crystal analysis. The crystal structure revealed that the Re(CO)(3) coordinates to two of the three inner nitrogens and one selenium to produce compound 3. The selenophene ring bent towards the Re(I)ion and the selenium is displaced by 0.41 angstrom from the mean plane of 24-atoms to coordinate with Re(I)ion in eta(1)-fashion. The 21-selenaporphyrin is distorted in compound 3 compared to free base 21-selenaporphyrin. H-1 and C-13 NMR studies indicated that compound 3 exhibits fluxional behaviour in coordination mode of binding in solution. The compound 3 is highly stable and does not undergo decomplexation under acidic conditions. The absorption spectra showed three broad Q-bands and splitted Soret band and electrochemical studies indicated that compound 3 is stable under redox conditions.

Synthesis of 3,5-Bis(acrylaldehyde) boron-dipyrromethene and application in detection of cysteine and homocysteine in living cells - Madhu, Sheri; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Journal Of Organic Chemistry, 2013)
Synthesis, characterization, and spectral and electrochemical properties of 3,5-bis(acrylaldehyde) BODIPY are described. The compound exhibited higher selectivity toward cysteine/homocysteine than toward other amino acids and thiol-containing compounds as shown by absorption and emission titration experiments and by experiments in living cells.

Synthesis, structure, spectral, electrochemical and sensing properties of 3-amino boron-dipyrromethene and its derivatives - Ganapathi, Emandi; Madhu, Sheri; Chatterjee, Tamal; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Dyes and Pigments, 2014)
We report the synthesis of 3-amino boron-dipyrromethene (3-amino BODIPY) by treating 3-bromo boron-dipyrromethene (3-bromo BODIPY) initially with sodium azide in acetonitrile followed by tri-phenylphosphine(PPh3)/H2O in tetrahydrofuran in three steps under mild reaction conditions. In this reaction, 3-azido BODIPY which formed in the first step was not isolated but the 3-iminophosphorane BODIPY which formed in the second step was isolated and characterized crystallographically. The 3-amino BODIPY was characterized by various spectroscopic and X-ray analytical techniques. To test the reactivity of amine functionality on BODIPY core, we prepared 1-(meso-anisyl BODIPY)-3-phenyl urea/thiourea derivatives under simple reaction conditions. Our studies indicated that 1-(meso-anisyl BODIPY)-3-pheny thiourea can act as specific chemodosimetric sensor for Hg2+ ion and 1-(meso-anisyl BODIPY)-3-phenyl urea as colorimetric and ratiometric sensor for F- ion. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: 3-Amino boron dipyrromethene; Chemodosimeter; F sensor; Fluorescent probes; Iminophosphorane BODIPY; Mercury(II) sensor